PENGARUH INTERVENSI PELAYANAN DAN DISAIN FASILITAS PELAYANAN TERHADAP MINAT PEMBELIAN ULANG Studi pada Toko Alfa Mart Yogyakarta - Yuni Istanto (UMSurabaya Publishing, 2007)
This research is a replica of the impact of costumer service intervention & facility design on firm performance “By Sulek, Lind, and maruchek (1995) and “ An assessment of the relationship between service quality science and costumer satisfaction in the formation of costomer’s purchase intention” by Taylor & Baker (1994). The purpose of this replica researchis caused by the competition of a retail industry which increases rapidly and if the customer satisfaction doesn’t gat a retail attention, the selling & profiy marginlevel go downrapidly, so this research will test the factors which are related to the relaton of the custumer satisfaction that is done by the intervention and service facility design and then it will test the influence of interest/intention the replica done in this research is not the whole replica,but it is modified and adapted to the Indonesian condition specilly in Yogyakarta.